2012
DOI: 10.1016/j.ajhg.2011.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in KIF11 Cause Autosomal-Dominant Microcephaly Variably Associated with Congenital Lymphedema and Chorioretinopathy

Abstract: We have identified KIF11 mutations in individuals with syndromic autosomal-dominant microcephaly associated with lymphedema and/or chorioretinopathy. Initial whole-exome sequencing revealed heterozygous KIF11 mutations in three individuals with a combination of microcephaly and lymphedema from a microcephaly-lymphedema-chorioretinal-dysplasia cohort. Subsequent Sanger sequencing of KIF11 in a further 15 unrelated microcephalic probands with lymphedema and/or chorioretinopathy identified additional heterozygous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
135
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(144 citation statements)
references
References 24 publications
8
135
0
1
Order By: Relevance
“…The predominant phenotype for mutations of this gene is late-onset fourlimb involvement, but there is a wide diversity in age of onset and extent of limb involvement (20). Additional genes, very recently identified, are GATA2 (21) and KIF11 (22). GATA2 causes Emberger syndrome and is interesting because of the relationship between lymphedema, immunodeficiency, and myelodysplasia, the latter predisposing to acute myeloid leukemia.…”
Section: Figurementioning
confidence: 99%
“…The predominant phenotype for mutations of this gene is late-onset fourlimb involvement, but there is a wide diversity in age of onset and extent of limb involvement (20). Additional genes, very recently identified, are GATA2 (21) and KIF11 (22). GATA2 causes Emberger syndrome and is interesting because of the relationship between lymphedema, immunodeficiency, and myelodysplasia, the latter predisposing to acute myeloid leukemia.…”
Section: Figurementioning
confidence: 99%
“…Based on the variability of features observed in some families, several authors have argued that autosomal dominant microcephaly with chorioretinopathy and the lymphedema, microcephaly, and chorioretinopathy syndrome may represent variable expressions of the same entity. Ostergaard et al [8] analyzed the KIF11 gene in unrelated chorioretinal dysplasia, microcephaly and mental retardation syndrome (CDMMR) and MLCRD syndrome families identified heterozygous mutations in KIF11 gene. It was concluded that the MLCRD and CDMMR syndromes should be considered a single entity with variable clinical features.…”
Section: Discussionmentioning
confidence: 99%
“…Microcephaly-chorioretinopathy-lymphoedema-mental retardation is associated with alterations in the KIF11 gene 15 and follows an autosomal dominant pattern of inheritance. It is included in this section as there is a very high incidence of congenital lower limb lymphoedema (46%).…”
Section: Microcephaly-chorioretinopathy-lymphoedema-mental Retardationmentioning
confidence: 99%